2011
DOI: 10.4314/wsa.v37i5.10
|View full text |Cite
|
Sign up to set email alerts
|

Development of guidance for sustainable irrigation use of greywater in gardens and small-scale agriculture in South Africa

Abstract: Greywater is untreated household effluent from baths, showers, kitchen and hand-wash basins and laundry (i.e. all non-toilet uses). More than half of indoor household water is normally used for these purposes and can potentially be intercepted by the householder for additional beneficial uses. Greywater use is practised on an informal basis to supplement irrigation water, either in urban gardens in middle-to upper-income suburbs or in food gardens in lower-income informal, periurban and rural areas. It holds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…A study by Bakare et al [35] in a Durban community showed a greater willingness to use greywater for toilet flushing and garden purposes at times of drought or water scarcity, and predominantly among younger participants (20-to 29-years-old). Rodda et al [36] evaluated the impact of medium-term sub-surface irrigation of vegetable crops with domestic greywater on soil, plant growth and yield, and microbiological quality of crops. The study concluded that greywater irrigation increased plant growth and crop yield.…”
Section: Ua In Low-income Settlements In South Africamentioning
confidence: 99%
“…A study by Bakare et al [35] in a Durban community showed a greater willingness to use greywater for toilet flushing and garden purposes at times of drought or water scarcity, and predominantly among younger participants (20-to 29-years-old). Rodda et al [36] evaluated the impact of medium-term sub-surface irrigation of vegetable crops with domestic greywater on soil, plant growth and yield, and microbiological quality of crops. The study concluded that greywater irrigation increased plant growth and crop yield.…”
Section: Ua In Low-income Settlements In South Africamentioning
confidence: 99%
“…Furthermore greywater is also a potential source of nutrients for plant growth, particularly for users who cannot afford fertiliser, and the soapy nature of greywater means that under some conditions it may act as a pest-repellent (Rodda et al, 2011). Greywater is, however, inherently variable in quality and as is most likely to be applied on a scale where quality monitoring is not feasible (Rodda et al, 2011). A range of contaminants may cause disease and have a negative impact on the environment.…”
Section: Greywater Reusementioning
confidence: 99%
“…Water re-use in both rural and urban environments is an essential strategy to overcome the looming water scarcity in South Africa (Ghunmi et al, 2011;Rodda et al, 2011); however, the data presented in Table 3 suggest that information on water re-use may not be filtering down to the public. Public awareness around water re-use and its necessity is essential since the threat of water insecurity is further complicated by the interdependency between water, energy and food production and consumption.…”
Section: Challenges and Knowledge Gapsmentioning
confidence: 64%